ANALISIS DAMPAK VARIABEL MAKRO EKONOMI TERHADAP INDEKS SAHAM SYARIAH INDONESIA (ISSI) - Siti Aisiyah Suciningtias; Rizki Khoiroh (Conference In Business, Accounting, And Management (CBAM), 2015)
Islamic capital market in Indonesia is growing significantly. The existence of the islamic capital market is characterized by the establishment of the Jakarta Islamic Index (JII) in 2000. The next development when in may 2011, the islamic capital market launched a new index namely is Indonesia Sharia Stock Index (ISSI). Indonesia Sharia Stock Index (ISSI) is a stock index that reflects the overall Islamic stocks listed on stock exchanges in Indonesia. Indonesia Sharia Stock Index (ISSI) is formed with a reason to separate between Islamic stock with stock instead of sharia. Previously mixed together in the Composite Stock Price Index, in Indonesia namely IHSG. Indonesia Sharia Stock Index devolopement shows a positive trend. There are many factors that affect the growth of Indonesia Sharia Stock Index (ISSI), can be seen from internal and external side. The data used in this study secondary data, time series, with the amount of data as much as 43 periods. The analysis technique used is multiple linear regression analysis. The results showed that the variable inflation and exchange rate has a negative and significant impact on Indonesia Sharia Stock Index (ISSI). However, the variable Bank Indonesia Certificates Sharia (SBIS) and world oil prices, they do not have a significant influence on the Indonesian Sharia Stock Index. The result of the determination coefficient adjusted R2 values of 0.203 or 20.3%. This shows that the model used in this study's weak in describing the effect of independent variables on the movement of Indonesian Sharia Stock Index (ISSI). Keywords: Indonesian Sharia Stock Index (ISSI), Inflation, Exchange Rates, Bank Indonesia Certificates Sharia (SBIS), World Oil Prices.